The transforming leader : new approaches to leadership for the twenty-first century - Pearson, Carol, 1944- (BK business book., 2012)
Outlines a new leadership approach tailored to the realities of the twenty-first century. Features chapters by such leading authors as Matthew Fox, Diana Whitney, and Alan Briskin. Edited and annotated by the author of the bestselling The Hero Within. The traditional model of the heroic leader single-handedly piloting the organization was always something of a myth, but it is especially unrealistic now. We live in a complex, fast-evolving, highly connected world. There is simply too much for a single person to keep track of or to address successfully. Leaders today must not only optimize all their own faculties, mind, body, and spirit, they must harvest the full capacities of those around them. To discover what leadership models are working now, the prestigious Fetzer Institute, along with the University of Maryland's School of Public Policy, and the International Leadership Association, brought together an impressive, interdisciplinary group of scholars and practitioners. The group drew on psychology, sociology, neuroscience, organizational change theory, myths and wisdom traditions, social networking theory, and the actual experiences of successful leaders to discover how leaders today achieve transformational results. The first part of the book offers an overview of what transformational leadership is, how it works, and how it is evolving. The second part shows readers how to increase cognitive complexity, link up their conscious and unconscious minds, and lead in ways that connect mind, heart, and spirit. The third part describes ways of leading groups to harvest collective wisdom and promote coordinated performance in the service of transformational ends. The conclusion explores how transformational communication can anchor new learnings so that they become habitual. Overall, The Transforming Leader reframes the challenge of leading in today's interdependent, unpredictable world. Its message is that if we update our thinking, enhance the quality of our being, deepen our sense of relatedness with the ecology of our natural and social worlds, and practice transformational communication, things no longer have to be so hard.